Neuromuscular electrical stimulation of the quadriceps in patients with non-small cell lung cancer receiving palliative chemotherapy: a randomized phase II study. - Matthew Maddocks; Vanessa Halliday; Alpna Chauhan; Victoria Taylor; Annmarie Nelson; Cathy Sampson; Anthony Byrne; Gareth Griffiths; Andrew Wilcock (PLoS ONE)
Background A reduced exercise capacity is associated with increased morbidity and mortality in patients with advanced non-small cell lung cancer (NSCLC). Therapeutic exercise can be beneficial and neuromuscular electrical stimulation (NMES) of the quadriceps muscles may represent a practical approach. The primary aim of this study was to determine the acceptability of NMES of the quadriceps to patients with NSCLC used alongside palliative chemotherapy. Secondary aims explored aspects of safety and efficacy of NMES in this setting. Methods Patients with advanced NSCLC due to receive first-line palliative chemotherapy were randomized to usual care with or without NMES. They were asked to undertake 30 minute sessions of NMES, ideally daily, but as a minimum, three times weekly. For NMES to be considered acceptable, it was predetermined that ≥80% of patients should achieve this minimum level of adherence. Qualitative interviews were held with a subset of patients to explore factors influencing adherence. Safety was assessed according to the Common Terminology Criteria for Adverse Events. Quadriceps muscle strength, thigh lean mass, and physical activity level were assessed at baseline and after three cycles of chemotherapy. Results 49 patients (28 male, median (IQR) age 69 (64-75) years) participated. Of 30 randomized to NMES, 18 were eligible for the primary endpoint, of whom 9 (50% [90% CI, 29 to 71]) met the minimum level of adherence. Adherence was enhanced by incorporating sessions into a daily routine and hindered by undesirable effects of chemotherapy. There were no serious adverse events related to NMES, nor significant differences in quadriceps muscle strength, thigh lean mass or physical activity level between groups. Conclusions NMES is not acceptable in this setting, nor was there a suggestion of benefit. The need remains to explore NMES in patients with cancer in other settings. Trial registration Current Controlled Trials ISRCTN 42944026 www.controlled-trials.com/ISRCTN42944026.